DESAIN PENGUATAN KUALITAS POLITIK DINASTI DALAM PEMILIHAN KEPALA DAERAH - Ahmad Siboy (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2021)
The purpose of this reseach is to describe the factors and implications of the proliferation of political dynasties and to find designs to create dynastic politics that do not conflict with the spirit of local democracy in Indonesia. The problem of this research is the factors and implications that make politics flourish in simultaneous Pilkada and the ideal dynastic political design. The research method used is normative juridical through the concept of an approach, legislation, case approach and historical approach. The results showed that dynastic politics mushroomed because the regional head as the ruler was unable to run again, the ruler at the national level wanted to use his power to place family members as rulers at the regional level. As a result, many candidates for regional heads are nominated without the competence and willingness to become regional heads. The ideal dynastic political design can be achieved with the requirements to be declared valid as a candidate for regional head as well as regulations that prevent unqualified regional head candidates from fulfilling formal or legal requirements as regional head candidates.